Model of Using Tiktok’s UGC as a New Media Political Communication Strategy for The 2024 Presidential Election in Indonesia - Prabu Revolusi (Greenation International Journal of Law and Social Sciences, 2023)
This research explores the use of TikTok as a new tool for political communication strategy in the context of the 2024 Presidential Election in Indonesia, focusing on the User Generated Content (UGC) model and the role of "Proxy" as a key component. The concept of UGC emphasizes how social media, particularly TikTok, influences political dynamics by allowing active public contribution to creating and disseminating political content that can shape public opinion. In the new media era, the Two-Step Flow Model and its modifications illustrate a shift from direct message transmission from opinion leaders to followers towards a more complex integration where opinion leaders and influencers interact not only with their followers but also with mass media through UGC. The research methodology employed is qualitative with a phenomenological approach, enabling researchers to delve into how TikTok is used to disseminate political information and shape public opinion. Data collected and analyzed aim to understand new constructions in political communication through UGC in the digital context. The study indicates that TikTok plays a crucial role in political communication strategy in Indonesia, where its success or failure can significantly impact public perceptions of political candidates. Findings provide a foundational basis for strategic recommendations to enhance the effectiveness of political campaigns in an era of rapid technological advancement. Overall, this research not only reveals the evolution of political communication strategies in the digital age but also offers valuable insights for the development of future political campaigns in Indonesia. The intensive use of social media platforms like TikTok as tools to influence public opinion and voter choices is increasingly becoming a critical strategy that needs careful management by political actors and their campaign teams.